Effect of air humidity and temperature on the thermal conductivity coefficient of perlite plasters - Szostak, Bartosz; Trochonowicz, Maciej; Hendzel, Paulina (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
The purpose of this article is to present the issue related to the influence of air humidity and temperature on the value of thermal conductivity coefficient of perlite plasters. Laboratory tests made it possible to determine the value of λ coefficient depending on the test temperature and air humidity (RH). From the measurements, the sorptivity and density of the materials were determined, as well as the flexural and compressive strength of the samples.